Algorithmic information theory in the stock market - Loh, Kenneth (2019)
The paper aims to study the various applications of algorithmic complexity on the stock market, and to evaluate the efficiency of each aspect. The efficiency is measured by the compression rate applied to simulated as well as real world data. The approach differs from typical price modelling which is based on an assumed stochastic nature of the market.